2015
DOI: 10.2478/s11696-014-0542-x
|View full text |Cite
|
Sign up to set email alerts
|

Biosensors containing acetylcholinesterase and butyrylcholinesterase as recognition tools for detection of various compounds

Abstract: Acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) are enzymes expressed in the human body under physiological conditions. AChE is an important part of the cholinergic nerves where it hydrolyses neurotransmitter acetylcholine. Both cholinesterases are sensitive to inhibitors acting as neurotoxic compounds. In analytical applications, the enzymes can serve as a biorecognition element in biosensors as well as simple disposable sensors (dipsticks) and be used for assaying the neurotoxic compounds. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 126 publications
0
18
0
Order By: Relevance
“…On the other hand, it does not mean that BChE is completely useless. It is able to degrade some toxic compounds of natural origin as well as drugs such as cocaine and succinylcholine (Duysen & Lockridge, 2011;Lejus et al, 2006;Pohanka, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it does not mean that BChE is completely useless. It is able to degrade some toxic compounds of natural origin as well as drugs such as cocaine and succinylcholine (Duysen & Lockridge, 2011;Lejus et al, 2006;Pohanka, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We investigated effect of boldine on both cholinesterases and found out that it is able to inhibit them. Dixon plot revealed noncompetitive mechanism of inhibition which is the most common inhibition mechanism for cholinesterases [ 13 ]. The inhibition of AChE by boldine was already investigated and authors reported IC 50 8.5 μ mol/l [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…Glucose biosensors have been widely researched and used even though it was the first and the most commercialized type (Turner 2013;Pohanka 2015).…”
Section: Current Construction Of Glucose Biosensorsmentioning
confidence: 99%